2001
DOI: 10.1002/1097-4598(200101)24:1<77::aid-mus9>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic restoration of dystrophin to dystrophin-deficient myotubes

Abstract: Dystrophin domains are observed in myoblast transplantation experiments and in muscle fibers after somatic reversion in human Duchenne and mdx mouse muscular dystrophy. However, the formation and evolution of dystrophin‐positive domains are not well established. Using a muscle satellite cell coculture system, we examined the dynamic restoration of dystrophin expression in dystrophin‐deficient myotubes. The dystrophin‐positive domains around source nuclei were clearly identified in hybrid myotubes. The occurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 51 publications
2
17
0
Order By: Relevance
“…We observed that the domain of each myoblast nucleus enlarges during growth in culture, and that dystrophin diffuses along myotubes prior to the organization of a mature fibre cytoskeleton that is localized immediately inside the sarcolemma (Kong and Anderson, 2001).…”
Section: Satellite Cells In Muscle Plasticitymentioning
confidence: 87%
“…We observed that the domain of each myoblast nucleus enlarges during growth in culture, and that dystrophin diffuses along myotubes prior to the organization of a mature fibre cytoskeleton that is localized immediately inside the sarcolemma (Kong and Anderson, 2001).…”
Section: Satellite Cells In Muscle Plasticitymentioning
confidence: 87%
“…Incorporated donor nuclei may supply only a limited amount of dystrophin that covers the limited area designated the nuclear domain of a host myofiber (Kong and Anderson, 2001). Therefore, incorporation of a large number of donor nuclei into host myofibers is required to produce amounts of dystrophin adequate to be distributed over the whole area of the plasma membrane of a host fiber.…”
Section: Fig 9 Round Cells Divide Slowly and Generate New Round Celmentioning
confidence: 99%
“…Qu-Petersen et al demonstrated restoration of dystrophin production in mdx mice (a mouse model of DMD which has a point mutation within its dystrophin gene) after transplantation of allogenic MDSCs [37]. Similar results were obtained by injecting satellite cells, mesoangioblasts and pericytes in high densities in to dystrophic muscle [52,66,67]. More recently, attention is focused on the use of genetically modified MDSCs, e.g.…”
Section: Regeneration Of Skeletal Musclementioning
confidence: 88%